APPLICATION OF DISCUSSION METHODS TO IMPROVE STUDENT LEARNING OUTCOMES IN CLASS IV STUDENTS IN SDN 084 CIKADUT - Agustina, Aneu; Maryati, Neng Sri; Altaftazani, Deden Herdiana (IKIP Siliwangi, 2018)
This study aims to determine the improvement of student learning outcomes in learning by applying the use of discussion methods in social studies learning with the subject of the map. This research was carried out by applying Classroom Action Research. With the research subject of IVA grade students of SDN 084 Cikadut Bandung with the number of students 20 students. The instruments used in conducting the study included observation sheets of teacher interaction, student interaction, test sheets, interviews and questionnaires on student attitude scale. Based on data analysis, it can be concluded that learning by applying the discussion method implemented in three cycles shows an increase in student learning achievement in each cycle. Student Worksheets in cycle 1 are 36% of students who complete learning, cycle 2 56% of students who achieve completeness. Next on the Worksheet 1 cycle group 61% of students completed, cycle 2 84% of students completed. So that it can prove that the application of the discussion method to improve the learning outcomes of fourth grade students in social studies subjects with the main discussion of maps can be carried out quite well and the results of each student have their respective improvements.